SPEECH ACT FOUND IN GENDER’S STATUS UPDATES OF FACEBOOK’S GROUP “FIB-UB 2010” - PRATAMA, YUDA NUR CAHYA PUTRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Speech Act, Facebook, Status Updates and Gender Speech act is an act performed behind the utterance. Speech act is a part of Pragmatics which is included into Macro Linguistic. In this modern era, technology always develops. One of the products of the technology development is social media. Simply put, by using social media people can communicate with others in simple way. Facebook is a social media which has many users around the world. This research uses Facebook as the object of research. The researcher analyzes status updated posted by the members of Facebook’s Group “FIB-UB 2010” using speech act theory. The researcher wants to know type of illocutionary act which found in status updates posted by the members of the group. The researcher also wants to know the dominant type of illocutionary act found in this group. In this research, the researcher divides the members of the group based on their gender to make easy classification of their status updates.The result of the research shows that in Facebook’s Group “FIB-UB 2010”, most status updates whether posted by male or female members, was included into type of illocutionary act called directive. Directive are acts used by the speaker to get the addressee to do something. So mostly status updated consist of some acts which belonged into directive such as request and order. The researcher argues, the possible reason why directive becomes the dominant type is that the data taken in academic situation where the members of the group was looking for information about their thesis project.For the next researchers who look for same object and same classification (gender) to be analyzed, they are suggested to focus on one act of illocutionary act such as act of requesting and try to find out the correlation between act of requesting that produced by male and female members with gender. So that, the next researcher will used speech act to analyze the act, and will continue by using sociolinguistic approach to find out the correlation of act with gender difference.